Pelatihan dan Penguatan UMKM Pembuatan Sabun Sunlight untuk Pemberdayaan Ekonomi Masyarakat Desa Jandi Meriah - Widya Ananda; Nurul Fazira Nasution; Tyo Nugro Diningrat; Arlina Arlina (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to improve the economic empowerment of the Jandi Meriah Village community through training and strengthening micro, small, and medium enterprises (MSMEs) in the production of Sunlight soap. This activity was implemented through the Real Work Lecture (KKN) program of the State Islamic University of North Sumatra in 2025. The main problems faced by the community are low household income and minimal entrepreneurial skills. The implementation method of this activity includes socialization stages, technical training on soap making, production assistance, and evaluation of the results of the activity. The results of the activity showed an increase in participants' knowledge and skills in making environmentally friendly liquid soap, as well as the growth of initiatives to form independent business groups based on home industries. This activity contributes to opening new business opportunities and strengthening the creative economy of rural communities.